The Cambridge ancient history / Vol. 11 The High Empire, A.D. 70 - 192 / ed. by Alan K. Bowman ... - Bowman, Alan K. (The Cambridge ancient history, 2000)
Volume XI of the second edition of The Cambridge Ancient History covers the history of the Roman empire in the period from AD 70 to 192, from Vespasian to the Antonines. The volume begins with the political and military history of the period. Developments in the structure of the empire are then examined, including the organisation and personnel of the central government and province-based institutions and practices. A series of provincial studies follows, and the society, economy and culture of the empire as a whole are reviewed in a group of thematic chapters. This edition is entirely rewritten from the 1936 edition. There is much more extensive discussion of social, economic and cultural issues, reflecting trends in modern scholarship, and the increase of archaeological evidence and development of new approaches to it. New documentary evidence, from texts on stone, wood and papyrus, has advanced knowledge in every chapter
Keywords: Geschichte; Römisches Reich